2019
DOI: 10.3390/nu11091966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anthocyanin-Rich Tart Cherry Extract on Inflammatory Mediators and Adipokines Involved in Type 2 Diabetes in a High Fat Diet Induced Obesity Mouse Model

Abstract: Male C57BL/6J mice were used to determine the possible therapeutic effects of our previously described tart cherry extract in a chronic obesity mouse model on metabolic parameters, glucose tolerance, inflammatory mediators, and antioxidant capacity. The control group received standard mouse chow, and the high fat control group was switched to a high fat diet and tap water supplemented with 5% sucrose. The high fat + anthocyanin group received the high fat and sucrose diet, but received the anthocyanin-rich tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 77 publications
(92 reference statements)
4
43
0
Order By: Relevance
“…The purified cyanidin 3-glucoside used in the diet of the rats has found to stimulate adipocytokine (leptin and adiponectin) secretion in the adipose tissue (Nemes et al, 2019). But, there are also the findings in which the different correlation between leptin and adiponectin was found.…”
Section: Leptin Activitymentioning
confidence: 99%
“…The purified cyanidin 3-glucoside used in the diet of the rats has found to stimulate adipocytokine (leptin and adiponectin) secretion in the adipose tissue (Nemes et al, 2019). But, there are also the findings in which the different correlation between leptin and adiponectin was found.…”
Section: Leptin Activitymentioning
confidence: 99%
“…Nemes et al [ 72 ] found that the intervention of anthocyanin-rich tart cherry extract effectively improved the antioxidant capacity of high-fat-diet-fed (45% energy from fat in diet and 5% sucrose in water) mice, but failed to retain body mass and glucose tolerance. Levels of IL-6 and leptin were reduced in the treatment group compared to control.…”
Section: Anthocyanins and Obesitymentioning
confidence: 99%
“…Flame Ionization Detector (FID) was used for identification of oligosaccharides. Anthocyanins supplement (TS6) was determined as Nemes et al [163] Anthocyanins were extracted from Hungarian sour cherry. Cherries were deseeded and homogenised, then methanol:water:acetic acid solution in 25:24:1 ratio was utilized to extract anthocyanins.…”
Section: Determination Of Natural Feed Additivesmentioning
confidence: 99%